OF BLACK BOXES, INSTRUMENTS, AND EXPERTS: TESTING THE VALIDITY OF FORENSIC SCIENCE. - MNOOKIN, JENNIFER L. (Episteme (Edinburgh University Press), 2008)
This paper argues that judges assessing the scientific validity and the legal admissibility of forensic science techniques ought to privilege testing over explanation. Their evaluation of reliability should be more concerned with whether the technique has been adequately validated by appropriate empirical testing than with whether the expert can offer an adequate description of the methods she uses, or satisfactorily explain her methodology or the theory from which her claims derive. This paper explores these issues within two specific contexts: latent fingerprint examination and the use of breath tests for the detection of alcohol. Especially in the forensic science arena, I suggest courts have often been seduced by superficially plausible explanations and descriptions of a technique or method, and permitted these to serve as a substitute for empirical testing. Thinking through these two examples illustrates both why evaluating the extent of testing should be the most important method by which courts assess reliability, and why, when other forms of explanatory evidence are readily available, we may nonetheless elect to make use of them. This paper suggests that these descriptions and explanations may at times usefully supplement evidence of testing, but should not generally be substituted for it. Finally, this paper embraces a kind of evidentiary pragmatism, in which the quantum of evidence required to establish legal reliability is determined not in the abstract, but in relation to the evidence that is, or ought to be, available as a result of reasonable research and investigation.